PENGARUH PENGGUNAAN APLIKASI HIRAGANA MEMORY HINT DALAM MENINGKATKAN KEMAMPUAN HURUF HIRAGANA SISWA SMAN 9 PEKANBARU - Silvia Hildebertha Panjaitan; Merri Silvia Basri; Dini Budiani (Universitas Negeri Padang, 2023)
This research is about the effect of Hiragana Memory Hint application in improving the Hiragana letters ability of the student of SMAN 9 Pekanbaru. This research is focused on one of the Japanese characters, namely Hiragana letters. The reason the researcher chose this letter was because the shape of the Hiragana letter was very different from the alphabet, making it difficult for students to memorize Hiragana letters. Therefore, an interesting, effective, efficient and fun media was tested, namely the Hiragana Memory Hint application. This application is based on Android so that students can use it on their respective cellphones and can be used anytime and anywhere as a medium for learning Hiragana letters. In this application there are various features such as animated images, sounds, and illustrations that are easy to understand, there is also a quiz feature to test how far the students' ability to recognize Hiragana letters. The purpose of this study was to determine the ability of Hiragana letters before and after using the Hiragana Memory Hint application for student at SMAN 9 Pekanbaru. This type of research is quantitative research using quasi-experimental method. Respondents in this study were students of class X SMAN 9 Pekanbaru and the research sample taken amounted to 40 people. Based on the results of the research that has been carried out, it is concluded of Hiragana Memory Hint application has an influence in increasing the ability of Hiragana letters for students at SMAN 9 Pekanbaru with an average value of 90,1.